2017
DOI: 10.18203/2349-2902.isj20172771
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile and its relevance in carcinoma breast

Abstract: Background: Breast cancer has emerged as a rapidly growing cancer in India and has already replaced cervical cancer. According to global cancer statistics for the year 2008, breast cancer resulted in 46 million deaths. In Asia, incidence rate of breast cancer is lower but is drastically rising. Nevertheless, while dyslipidemia [high LDL-C (low density Lipo-protein-cholesterol) and low HDL-C (high density lipo-protein-cholesterol) levels] has controversial role in this disease; the specific influence of dyslipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
(31 reference statements)
1
8
0
1
Order By: Relevance
“…Their study also showed that 66% patients were > 40 years old. [19] Another study done in Thailand by Pikul Laisupasin et al showed similar results. [20] Both the above mentioned studies were prospective comparative studies similar to our study type.…”
Section: Discussion:-mentioning
confidence: 69%
See 2 more Smart Citations
“…Their study also showed that 66% patients were > 40 years old. [19] Another study done in Thailand by Pikul Laisupasin et al showed similar results. [20] Both the above mentioned studies were prospective comparative studies similar to our study type.…”
Section: Discussion:-mentioning
confidence: 69%
“…It was a prospective comparative study similar to our study. [8] Another study was carried out in 2 years in Portugal by Catarina Rodrigues dos Santos and colleagues. It was a prospective study of 244 breast cancer patients and serum lipid profile was studied in these patients which showed positive association of LDL and TG with breast cancer.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that obesity, dyslipidemia [9], and Uricemia [10] have signi cant associations with cancer progression including cancer of the oral cavity [11] breast [12], colorectal, ovary, and prostate [13].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological, clinical and laboratory studies have made it possible to identify a group of probable risk factors, which exhibit a positive correlation with the disease onset [7]. Population studies have demonstrated that early menarche, late menopause, childlessness and not breastfeeding are breast cancer risk factors [8,9]. Increased incidence of neoplastic diseases is also known to be accompanied by lipid metabolism disorders [10].…”
Section: Introductionmentioning
confidence: 99%